Cost-effective aqueous-phase synthesis of long copper nanowires. Issue 102 (2nd October 2015) - Tang, Zengmin; Shahzad, Aasim; Kim, Woo-Sik; Yu, Taekyung
Abstract : This work describes a simple and cost-effective aqueous-phase synthesis of Cu nanowires with long-term stability. Chloride ions and branched polyethyleneimine (BPEI) were found to be of great importance to the formation and stabilization of Cu nanowires. Abstract : This work describes a simple and aqueous-phase route for the synthesis of Cu nanowires (Cu NWs) having a long length of 140−180 μm, a high aspect ratio of more than 350, and long-term stability. High-quality Cu NWs were synthesized by reduction of CuCl2 with ascorbic acid in the presence of branched polyethyleneimine (BPEI) in an aqueous solution at 90 °C. The synthesized uniform Cu NWs showed long-term stability without the formation of Cu oxides on the surface of the NWs after being stored at room temperature for 40 days. Interestingly, we found that Cl − in the reacting solution played a key role in the formation of long Cu NWs. We also investigated the influence of various experimental conditions including the weight ratio of BPEI/CuCl2, the pH of the reacting solution, and the reaction temperature on the length, morphology, and stability of Cu NWs.